Evaluation of okra [Abelmoschus esculentus(L)Monench] genotypes for yield resistance to shoot and fruit borer,Earias vittella(Fab) - Shrishail B Duggi (Department of Plant Breeding and Genetics, College of Agriculture, 2012)
The research project entitled “Evaluation of okra [Abelmoschus esculentus (L.) Moench] genotypes for yield and resistance to shoot and fruit borer, Earias vittella (Fab.)” was carried out in the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during the period 2011-2012. The study aimed at the evaluation of a collection of okra genotypes for shoot and fruit borer resistance and yield to identify high yielding shoot and fruit borer resistant genotypes, if available among them.